2012
DOI: 10.1177/0022034512460833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Calcium-silicate-based Restorative Cement on Pulp Repair

Abstract: In cases of pulp injury, capping materials are used to enhance tertiary dentin formation; Ca(OH)(2) and MTA are the current gold standards. The aim of this study was to evaluate the capacity of a new calcium-silicate-based restorative cement to induce pulp healing in a rat pulp injury model. For that purpose, cavities with mechanical pulp exposure were prepared on maxillary first molars of 27 six-week-old male rats, and damaged pulps were capped with either the new calcium-silicate-based restorative cement (Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
191
3
26

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(243 citation statements)
references
References 27 publications
23
191
3
26
Order By: Relevance
“…1,7,34,35 Ancak son zamanlarda araş-tırmacılar, MTA'nın yüksek maliyeti, çalışma zamanının uzunluğu ve dişte renklenmeye neden olması gibi dezavantajlarından dolayı CEM ve trikalsiyum silikat içerikli "Biodentine" materyallerini tek seans apeksifikasyon çalışmalarında kullanmışlardır. 11,14,36 İn vitro koşullarda materyallerin apikal örtü-cülük özelliklerinin değerlendirmesinde elekrokimyasal analiz, radyoizotop yöntemi, kimyasal ajanların kullanımı, basınçlı hava kullanımı, bakteri sızıntı yöntemi ve boyama yöntemi gibi pek çok sızıntı testi kullanılmaktadır. [37][38][39][40] Bu test yön-temleri içerisinde uygulanması kolay ve daha ekonomik olması nedeni ile en çok tercih edilen yöntem, boya sızıntı testidir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…1,7,34,35 Ancak son zamanlarda araş-tırmacılar, MTA'nın yüksek maliyeti, çalışma zamanının uzunluğu ve dişte renklenmeye neden olması gibi dezavantajlarından dolayı CEM ve trikalsiyum silikat içerikli "Biodentine" materyallerini tek seans apeksifikasyon çalışmalarında kullanmışlardır. 11,14,36 İn vitro koşullarda materyallerin apikal örtü-cülük özelliklerinin değerlendirmesinde elekrokimyasal analiz, radyoizotop yöntemi, kimyasal ajanların kullanımı, basınçlı hava kullanımı, bakteri sızıntı yöntemi ve boyama yöntemi gibi pek çok sızıntı testi kullanılmaktadır. [37][38][39][40] Bu test yön-temleri içerisinde uygulanması kolay ve daha ekonomik olması nedeni ile en çok tercih edilen yöntem, boya sızıntı testidir.…”
Section: Discussionunclassified
“…10,14,36 Literatür değerlendirmesinde immatür diş-lerde "Biodentine" materyalinin apikal örtücülük özelliği ile ilgili çalışma yapılmadığı görülmüştür. Çalışmamızda, "Biodentine" grubu MTA grubu ile sızıntı düzeyi açısından kıyaslandığında aralarında istatistiksel farklılık olmadığı görülmüştür (p=0,30).…”
Section: Discussionunclassified
“…Biodentine is another formulation used in practice in biological therapy, perforation, or as a substitute for dentin without the need for etching [19]. This preparation, like MTA, is classified as a bioceramic material -silica-calcium cement.…”
Section: Age-related Changes In Endodontiummentioning
confidence: 99%
“…It was introduced into dentistry in the 19 th century and since that time it has been commonly used in various indications, especially due to its strong alkalizing, antibacterial, antinflammatory potential as well as its capacity to stimulate pulpal regenerative processes [5][6][7][8][9][10]. The mechanism of action of calcium hydroxide products is based on its ability to dissociate in aqueous solutions into free Ca 2+ ions and hydroxyl ions which activate many chemical reactions in contact with vital tissue as well as provide a highly alkaline environment with pH of approximately 12.5 [5][6][7][8][9][10]. Free hydroxyl ions show enormous reactivity with many various biomolecules.…”
mentioning
confidence: 99%
“…The loss of restoration in the coronal part of the tooth, discolorations of hard tissues and reinfections were also observed after endodontic treatment [6,11,12,14]. Numerous studies [5,9,12,13] have revealed that dentinal bridges formed as a result of odontotropic processes are irregular and quite thin. They frequently include so-called tunnels (gaps), which may predispose the patient to infection of the pulp.…”
mentioning
confidence: 99%